Student’s need analysis in using ordinary differential equation e-module of Mathematical Physics II - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Fhadira Insani Putri; Rahmat Perdana; Fuldiaratman Fuldiaratman (Momentum: Physics Education Journal, 2023)
The purpose of this research is to find out students’ opinion about e-module ordinary differential equations that will be developed. This type of research is a mixed method with the purposive sampling technique. The samples were 50 students of Universitas Jambi majoring physics education a regular class A and regular class B 2020 who took the mathematical physics II course. The data were collected through interviews and questionnaires, then analyzed using descriptive statistics for the questionnaires and Miles and Huberman’s analysis for the interview results. The findings show that the majority of the students believe the creation of this e-module is a very good idea. This is proven by the results of descriptive statistics, where the average value is 18,0 and is in the required category. The quantitative findings are strengthened by the qualitative ones from interview, which show that the majority of respondents support the creation of this e-module. The results indicate that the students require additional learning resources to fully comprehend the lessons in the Mathematical Physics II e-module. Students can learn independently in mathematical physics course by using e-modules. The future studies on mathematical physics e-modules can use this study as a guide.